The Savvy Survey #6a: General Guidelines for Writing Questionnaire Items - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS)
This 6-page fact sheet gives an overview of important considerations to make when creating questionnaire items, such as: types of information that can be collected, parts of a question, and appropriate text and wording choices. It is part of the Savvy Survey Series. Written by Jessica L. Gouldthorpe and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, April 2014.